Features of a woman᾿s style company management - T. M. Gololobova (Вестник университета)
Gender studies of work effectiveness of male and female have being conducted for a long time. However, with the trend of the spread of equality, they become particularly relevant. It is impossible to say with certainty which manager is more effective. Both a woman and a man can be equally effective in any position. At the same time, it cannot be denied that there are significant differences between the male and female management style. They can be considered in a certain approximation, since there are always exceptions to the rules. The article examines the advantages and disadvantages of women’s management style, provides a typology of women managers, a criterion analysis of female and male management styles. And recommendations are also given on what points a female manager needs to work on in order to be more effective at work.